Letter to Jane Tolmach from Assemblywoman Teresa P. Hughes - Teresa P. Hughes:::::: (1976)
This June 10, 1976 mailgram from Assemblywoman Teresa P. Hughes congratulates Jane Tolmach on her victory. Hughes offered her assistance if needed and expressed that she looked forward to working with Tolmach in Sacramento.